EP697 Establishing the audit and research in gynaecological oncology (ARGO) collaborative in the united kingdom and ireland. (1st November 2019) - Wan, YL; Bharathan, R; Frost, J; MacKintosh, ML; Collaborative, ARGO
Abstract : Introduction/Background: Aims: To establish a collaborative to deliver and provide training in research and clinical audit in gynaecological oncology. Background: Trainee-led research collaboratives in general surgery have demonstrated the ability of such groups to rapidly recruit large numbers of patients and deliver high quality multi-centre research. Trainees are ideally placed to deliver research at point of care given the rotational nature of their placements, their established communication networks and the motivation to provide evidence for participation research and audit during their training. In Gynaecological Oncology, where care is centralised to tertiary level units, there is the opportunity to collect nationally impactful data. Methodology: Members were recruited through the British Gynaecological Cancer Society, National Cancer Research Institute, Royal College of Surgeons and Royal College of Obstetricians and Gynaecologists. A core committee was established to deliver group aims. Webinars and educational events were used to engage with members nationwide. A competitive call for multicentre projects allowed for the selection of our national project. Results: Between August and November 2018, 52 members, comprising trainees from all fourteen deaneries in the United Kingdom, Northern Ireland and the Republic of Ireland, were recruited. A core committee of six trainees was elected. Two online events and one face to face event have been held. Seven multi-centre project proposals were received. A masked expert panel short-listed four proposals for a ´dragon´s den´ presentation and refinement. Subsequently, the membership selected a project which will establish how frailty in older patients affects outcomes after gynaecological oncology surgery. Conclusion: There is a desire amongst trainees to engage in research to deliver patient benefit. A collaborative model facilitates efficient implementation of a project and yields nationally actionable information. Our next study will aid clinical decision-making in some of our most vulnerable patients. Disclosure: Nothing to disclose.